2009
DOI: 10.1161/atvbaha.109.189662
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy With Simvastatin and Bone Marrow–Derived Mesenchymal Stem Cells Increases Benefits in Infarcted Swine Hearts

Abstract: Objective-Widespread death of implanted cells hampers stem cell therapy for acute myocardial infarction (AMI). Based on the pleiotropic beneficial effects of statins, we examined whether simvastatin (SIMV) increased the efficacy of mesenchymal stem cell (MSC) transplantation after AMI. Methods and Results-Chinese miniswine (nϭ28) were randomized to 1 of 4 groups (nϭ7 per group): control, SIMV (0.25 mg/kg ⅐ d), MSC transplantation, and SIMVϩMSCs. AMI was created by ligating the left anterior descending coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 34 publications
3
59
0
1
Order By: Relevance
“…Our present results revealed that, compared with vehicle administration, 14 days of 10 mg/ kg/day Ator administration could not only decrease inflammatory cells infiltration, myeloperoxidase activity, the expression of inflammatory cytokine mRNA, and regulation of anti-and pro-apoptotic cytokines expression, but also improve cardiac function, as reflected by LVEF and CO elevation, and LVVs and HR reduction in the three Ator groups. Compared with the studies by Yang et al [11,19], there were some discrepancies needed to be addressed. First, the experimental model used by Yang was created by an ischemia-reperfusion procedure, while ours was permanent ligation of coronary artery.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our present results revealed that, compared with vehicle administration, 14 days of 10 mg/ kg/day Ator administration could not only decrease inflammatory cells infiltration, myeloperoxidase activity, the expression of inflammatory cytokine mRNA, and regulation of anti-and pro-apoptotic cytokines expression, but also improve cardiac function, as reflected by LVEF and CO elevation, and LVVs and HR reduction in the three Ator groups. Compared with the studies by Yang et al [11,19], there were some discrepancies needed to be addressed. First, the experimental model used by Yang was created by an ischemia-reperfusion procedure, while ours was permanent ligation of coronary artery.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, to provide support for the ability of transplanted cells to withstand the hostile microenvironment is an essential prerequisite for cardiac function improvement with MSCs transplantation. Yang et al [11,19] showed that Ator and simvastatin could improve MSCs' cardiac protection efficacy through amelioration of the cardiac milieu in an ischemic-reperfusion injury model. Ator and simvastatin are 3-hydroxy-3-methylglutaryl-CoA reductase inhibitors, with pleiotropic effects including anti-inflammatory activities, anti-oxidant properties, regulation of pro-and anti-apoptotic cytokine expression, protection of the endothelium, and regulation of endothelial progenitor cell migration and Figure 3 Evaluation of cardiac microenvironment parameters (A) A large number of inflammatory cells infiltrating in peri-infarct areas, and the number of inflammatory cells was less in the three Ator groups than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that statins could potentiate the activation of many pro-survival pathways, however, the activation of only a few pro-survival pathways have been demonstrated in neuronal systems [73]. Other pro-survival activation has been demonstrated using cardiac and stem cells [74]. Fig.…”
Section: Anti-apoptotic Signaling Pathways Of Statins In Admentioning
confidence: 99%
“…They can not only attenuate the inflammation and oxidative stress to provide a better microenvironment for implanted MSCs after AMI, but also increase the anti-apoptotic capacity of MSCs itself under H/SD condition, of which, both make statins a convincing candidate to deal with the ''low survival'' problem of MSCs mentioned previously [3,[13][14][15]. Several signaling pathways have been implicated in this protective role of statins, including AMP-activated protein kinase (AMPK), Janus kinase/ signal transducers and activators of the transcription, phosphatidylinositol 3-kinase (PI3K)/Akt, and mitogen-activated protein kinase/extracellular signal-regulated kinase (MEK/ ERK1/2) pathways [13,14,16].…”
Section: Introductionmentioning
confidence: 99%